Differences in Stress and Coping During the COVID-19 Pandemic in Families With and Without Children With Developmental Disorders or Chronic Conditions - Martinsone, Baiba; Tzivian, Lilian (Frontiers in Public Health, 2021)
Objectives: To compare COVID-19-induced stress and coping in families with and without children diagnosed with developmental disorders or chronic conditions. Methods: In this mixed-method design study, an online survey collected information on parental stress levels before and during COVID-19, sources of stress, and coping strategies using open-ended questions. Qualitative answers were categorised thematically. Multiple linear regression models were built for the association between changes in stress levels (during-before COVID-19) and sources of stress for parents of children of both groups. Results: Answers of 1827 parents were analysed; of these, 186 (9.75%) had children with diagnosed problems. Changes in stress levels during vs. before COVID-19 were associated with the age of the parent, changes in working conditions, a total number of stressors, and distance learning of children. Stronger associations were found for parents of children with diagnoses. For example, for distance learning, the standardized beta (β) was 0.68 [95% confidence interval 0.37; 1.00] for parents of children without problems and β=0.73 [0.43; 1.03] for those with problematic children. Conclusions: Parents of children with developmental disorders need specific attention in a pandemic.